Poškodbe zdravstvenih delavcev z ostrimi predmeti - Kosten, Tatjana (Obzornik zdravstvene nege, 2006)
The article brings the survey of literature on injuries of health workers and the analysis of injuries of health workers of the Hospital Golnik, Clinical Department for Lung Diseases and Allergy. By keeping track of injuries of health workers and the analysis of these data, we tried to find causes of injuries and to prevent them with education of health workers, by the use of containers for sharp objects, by use of safe techniques and work procedures. All these measures are aimed at bigger safety of the employees.
Keywords: Epidemiology; Igla, vbodnine; Needlestick Injuries; Occupational Exposure; Poklicna izpostavljenost; poškodbe; preprečevanje; zdravstveni delavci